Information seeking, technology use, and vulnerability among migrants at the United States-Mexico border - Newell, Bryce Clayton; Gomez, Ricardo; Guajardo, Verónica E. (The Information society, 2016)
Through interviews with migrants and migrant aid-workers at a shelter in the border town of Nogales, Mexico, we examine how undocumented migrants are seeking, acquiring, understanding, and using information prior to, and during, migration across the United States-Mexico border. Our study examines migrants' perceptions of humanitarian service and the use of so-called "border disturbance technologies" by activists to help prevent the death of migrants in the desert, finding that migrants appreciate water-caching efforts but generally distrust technologies they feel could subject them to surveillance by border agents. Exploratory in nature and based on a small sample, our findings are not necessarily representative of the broader population, but provide rich evidence of the prevalence of word-of-mouth information seeking and use of cell phones over other information technologies, and explore the ambivalent nature of information technology use in the vulnerable setting of life at the border. In particular, we find that mobile phones help migrants meet their communication needs, but also increase their exposure to crime and abuse.